TINDAK TUTUR ILOKUSI PADA IKLAN PINJAMAN ONLINE DI YOUTUBE: PINJAM DI ADAKAMI SYARATNYA RIBET GAK SIH? - Romadoniyati Ruhhaidah Welliansyah; Any Budiarti; Marlia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The phenomenon of online loan advertising in recent years has become a hot topic of discussion in the community. This cannot be separated from the important role of language as a means of communication. The purpose of this study was to analyze the illocutionary speech acts contained in the online loan advertising video on YouTube entitled “Loans at Adakami are complicated or not?”. This study uses qualitative research methods with a descriptive approach. The results of the study found that in the online loan advertising there are 15 words that are illocutionary speech acts, dominated by assertive illocution as much as 9 (60%), expressive illocution as much as 3 (20%), directive illocution as much as 2 (13,33%), and commissive illocution as much as 1 (6,67%). While the directive illocution was not found.